Social and Behavioral Correlates of Sexually Transmitted Infections among Men who Have Sex with Men who Use Alcohol in the San Francisco Bay Area - Jain, Jennifer P. (Am J Mens Health, 2021)
The risk of acquiring sexually transmitted infections (STIs) among men who have sex with men (MSM) is driven by various socio-behavioral factors. From 2015-2017, 247 MSM ≥ 18 years-old who reported alcohol use in the past year, were recruited into a cross-sectional study in San Francisco. Participants completed a survey assessing socio-demographics, substance use and treatment, sexual behaviors, HIV status and self-reported STI diagnosis in the past 6 months. Multivariable logistic regression models stratified by HIV status were used to identify the correlates of STIs. Of 247 MSM, the prevalence of bacterial STIs were: gonorrhea (12.9%), chlamydia (9.3%) and syphilis (6.0%). Among 177 MSM living without HIV, factors significantly associated with recent STI diagnosis were: current pre-exposure prophylaxis (PrEP) use (aOR = 3.53, 95% CI: 1.42–8.75, p ≤ .01), popper use during sex in the past 6 months (aOR = 3.16, 95% CI = 1.34–7.47, p ≤ .01) and a history of alcohol treatment (aOR = 0.17, 95% CI = 0.04–0.68, p = .01). Also, in a sensitivity analysis (removing PrEP), any receptive condomless anal sex was independently associated with recent STI diagnosis (aOR = 2.86, 95% CI = 1.15–7.08, p = .02). Among 70 MSM living with HIV, factors significantly associated with recent STI diagnosis were: White race/ethnicity (adjusted odds ratio [aOR] = 7.36, 95% confidence interval [CI] = 1.48–36.62, p = .01), younger age (aOR = 0.90, 95% CI: 0.84–0.97, p < .01) and a higher number of male sexual partners in the past 6 months (aOR = 1.03, 95% CI = 1.00–1.06, p = .02). Sexual health interventions that address the unique needs of MSM living with and without HIV who use alcohol in San Francisco are needed to reduce STI acquisition and transmission.